Spiritual-Based Management: Accessibility Of Da'wah For The Visually Impaired In The DPD Pertuni Of North Sumatra - Tria Tanti; Nurhanifah (TASAMUH : Jurnal Komunikasi dan Pengembangan Masyarakat Islam, 2025)
Accessibility of da'wah is used to facilitate access to information on da'wah. Visually impaired people need accessibility of da'wah to make it easier to learn Islam. This study aims to explain the accessibility of da'wah in religious guidance programs for blind people with disabilities in PERTUNI North Sumatra by using spiritual management in managing activities to achieve effective and efficient goals. This research uses qualitative methods conducted at DPD PERTUNI North Sumatera with data collection techniques in observation and interviews. The subjects in this study were 5 instructors and 3 blind people. Data management uses 4 methods: data collection, reduction, presentation, and conclusion drawing. The results of this study indicate that the existence of religious guidance for the visually impaired has positive implications for themselves, not only in terms of religion but also in terms of their economic and social impact, so that this religious guidance program motivates for them to get out of a sense of adversity and backwardness to be empowered and take their role in social life. It ishoped that this research can be a recommendation for da'wah institutions in making special activities for the visually impaired and paying more attention to the scope of da'wah so that all people can feel it without exception